THE ECONOMY AND POVERTY REDUCTION; A DIMENSION OF HEALTH IN ISLAM - Angga Syahputra; Husna Hayati (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
Poverty and health have an inherent relationship like two sides of a coin. Poverty can make people live in poor health conditions, as well as poor health can make poverty. Individuals or communities who do not take care of their health conditions can encourage them to be trapped in increasingly severe conditions of poverty. Maintaining health includes self-care activities as commanded by Islam. Health is something that has a high level of urgency, because it has a direct impact on the economy. This study uses a qualitative method, using a literature review. The main data is obtained from previous studies, the results of the latest scientific publications and data published by the Central Statistics Agency. In order to create a healthy society, better management is needed from the Government in managing health programs and full support from the community in living a healthy life as taught by Islam.